PERSEPSI ORANG TUA TERHADAP PROGRAM INTERVENSI BAGI ANAK AUTIS - Nurul Mutahara B; Syamsuddin; Tatiana Meidina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine parents' perceptions of intervention programs for children with autism. Parents play a crucial role in supporting the success of intervention programs because they are directly involved in their children's daily development. This study used a descriptive qualitative approach. The subjects were parents of children with autism who participated in intervention programs at schools or therapy centers. Data collection techniques were conducted through interviews, observation, and documentation. The results showed that most parents had positive perceptions of the intervention program because they considered it capable of improving children's communication skills, social interactions, behavior, and independence. Parents also stated that the intervention program helped children become more responsive and able to adapt to their surroundings. However, several obstacles still exist, such as limited funds, limited time for support at home, and limited understanding of intervention strategies for children with autism. Therefore, good collaboration between parents, teachers, and therapists is needed to optimize the implementation of intervention programs for children with autism.